A Giant Mature Cystic Teratoma Mimicking a Pleural Effusion - Mustafa Erman Dorterler; Mehmet Emin Boleken; Sezen Koçarslan (Case Reports in Surgery)
The vast majority of teratomas originating from more than a single germ layer are benign. Often, such teratomas are initially asymptomatic. Later symptoms are caused by the weight per se of the teratoma and include chest pain, cough, dyspnea, and/or recurrent attacks of pneumonia. A mediastinal teratoma is treated by total surgical resection of the mass. Here, we report a case of giant mature cystic teratoma mimicking a pleural effusion in the thorax at the 7-month-old female patient with a symptom of persistent pulmonary infection and tachypnea.